Immune-mediated gastritis in a patient with breast cancer due to therapy with immune checkpoint inhibitor pembrolizumab: a case report - Xu, Yalan; Wang, Junyao; Chen, Ning (Frontiers in Oncology, 2025)
The use of immune checkpoint inhibitors (ICIs) in the treatment of malignant tumors is becoming more widespread, and the management of immune-related adverse events (irAEs) has become an important concern in oncological treatments. Here we present a 44-year-old female patient with triple-negative breast cancer (TNBC), who developed severe nausea and vomiting symptoms after pembrolizumab treatment. Gastroscopy showed extensive exfoliation, redness, and swelling of the gastric mucosa. Histology suggested complete destruction of the gastric mucosa and a large number of immune cells infiltration. After excluding other differential diagnoses, we considered the diagnosis of immune checkpoint inhibitor-associated gastritis. In responding to methylprednisolone treatment, her symptoms improved, and a repeated gastroscopy suggested repair in gastric mucosa, but demonstrated autoimmune gastritis-like manifestations. This case report describes a rare case of ICI-mediated gastritis. The importance of early endoscopy is emphasized and hormonal therapy remains the mainstay of treatment for this patient.